DETEKSI GEN TEMONEIRA (TEM) PADA URIN PENDERITA GAGALGINJAL KRONIK (GGK) SEBAGAI PENANDA RESISTENSI ANTIBIOTIK DENGANMENGGUNAKAN METODE POLYMERASE CHAIN REACTION (PCR) DI RSUD BAHTERAMAS PROVINSI SULAWESI TENGGARA - Syawal Abdurrahman; Sanatang; Shalsa Juniastrid Masiar (Prodi D4 Teknologi Laboratorium Medis, Universitas Mandala Waluya, 2025)
Chronic kidney disease (CKD) is a condition in which the kidneys experience a decline in kidney function. Chronic kidney disease (CKD) causes a decline in immunity, metabolism, and catheter use, which can increase the risk of urinary tract infections (UTIs). Urinary tract infections (UTIs) are common infections caused by the pathogenic bacterium Escherichia coli. The Temoneira (TEM) gene is one of the genes specifically associated with resistance to β-lactamase antibiotics. The objective of this study is to detect the TEM gene as a marker of antibiotic resistance in the urine of patients with chronic kidney disease using the Polymerase Chain Reaction (PCR) method. The type of research conducted was quantitative research. The population in this study consisted of 12 respondents with chronic kidney disease (CKD) at the Bahteramas Regional General Hospital in Southeast Sulawesi Province, while the sample size was 10 respondents, representing the entire population. The research methods included DNA isolation, DNA concentration measurement, TEM gene amplification, and visualization of the results using agarose gel electrophoresis. Based on the absorbance measurements of the DNA isolates, a DNA purity ratio below 1.8 was obtained, indicating protein contamination. DNA visualization results showed that there were 10 samples that exhibited an 861 bp DNA band, indicating the presence of the TEM gene as an antibiotic resistance marker. The conclusion of this study is that out of 10 respondents, there were 10 positive samples of the TEM gene, marked by the appearance of an 861 bp DNA band. Further research is recommended to continue using the DNA sequencing method to confirm the variation of the TEM gene mutation..